The functionality of aesthetic illusion and epistemic relativism in Grace Ogot’s The Strange Bride (1989) - Diallo, Souleymane (Research Journal in Advanced Humanities, 2022)
Throughout a dimensional analysis of rationality and a factual relativism justification, The Strange Bride upholds a temporal perspective and a neo-experience of present within which Grace Ogot methodic metafiction, defines a differential relational model regarding the Be-, the There-ness and norms of belief. This vigorous realm of interaction impels the inflection of alethic modality to stand as a meromorphic function; then, the illusion of time and the spacetime dimension dive the cosmological time, the metaphysic of time, the linguistic conception of time and contemporary cultural theory in a combinatorial set of a pluricellular function and a multifactorial understanding. Through the temporal structure and the representation of the continuum of spacetime, Ogot circumscribes a connectionism transformation; therefore, the form and the content of the Be-ing, the relationalism between space-time continuum and the there-ness dimension of creative imagination become an aesthetic and functional performance. In this dynamic, the problematic of the Be-ing object from the quantitative nominal properties of time characterizes, in this model of narrative, the metaphysic of presence and the cultural theory of time.